2020
DOI: 10.1038/s41598-020-74659-9
|View full text |Cite
|
Sign up to set email alerts
|

Relative fat mass at baseline and its early change may be a predictor of incident nonalcoholic fatty liver disease

Abstract: The relationship between changes in body components and the risk of nonalcoholic fatty liver disease (NAFLD) is not fully understood. We investigated the effects of body components and subsequent changes on incident NAFLD at follow-up ultrasound scanning in a longitudinal cohort. We included 9967 participants without NAFLD at baseline who underwent serial health examinations. Sex-specific, weight-adjusted skeletal muscle index (SMI_Wt) was used. Mean follow-up duration was 48.5 ± 33.5 months. NAFLD developed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
14
1
Order By: Relevance
“…Neither weight- nor height-adjusted SMI did however show the anticipated inverse association with NASH in this study, suggesting that sarcopenia in patients with obesity might not be the decisive factor for developing NASH. Confirming this, a large prospective cohort study found an increased risk for incident NAFLD in patients with overweight and obesity with higher FM at baseline, while lower SMI did not show a significant association with incident NAFLD during a mean follow-up of 48.5 months [ 15 ].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Neither weight- nor height-adjusted SMI did however show the anticipated inverse association with NASH in this study, suggesting that sarcopenia in patients with obesity might not be the decisive factor for developing NASH. Confirming this, a large prospective cohort study found an increased risk for incident NAFLD in patients with overweight and obesity with higher FM at baseline, while lower SMI did not show a significant association with incident NAFLD during a mean follow-up of 48.5 months [ 15 ].…”
Section: Discussionmentioning
confidence: 70%
“…The relation of sarcopenia with NAFLD and NASH has been subject of recent discussions [ 1 , 5 , 7 , 9 , 16 , 17 , 34 , 35 , 36 ]. This connection is especially interesting in patients with obesity and sarcopenic obesity (SO), as high amounts of visceral fat have been described to be predisposing for NAFLD and NASH [ 13 , 15 ]. The aim of this study was to assess the association of body composition and NASH in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional study in the Netherlands population reported that an increase of total fat mass was significantly associated with a higher risk of NAFLD both in participants with normal weight and in overweight [ 27 ]. A longitudinal study found that higher fat percentage at baseline may be a predictor of incident NAFLD across all obesity spectrum [ 28 ]. At the same time, emerging evidence suggested that the substantial loss of muscle mass, the main component of fat-free mass, termed as ‘sarcopenia’, had a negative effect on the risk of NAFLD and fibrosis independent of obesity.…”
Section: Discussionmentioning
confidence: 99%